Effects of Leadership Style on Employee Performance of Fast Moving Consumer Goods (FMCGS) in South Africa - Solomon OMONONA; Olabanji ONI; Joseph OBAMEN (Journal of Economics and Behavioral Studies, 2019)
Abstract: The study seeks to assess the effects of leadership style on Employee performance (EP) of fast moving consumer goods (FMCGs) companies in South Africa. The specific objectives are: to determine the effects of autocratic leadership style on EP; to evaluate the effect of participative/ democratic leadership style on EP; to ascertain the relationship between laissez faire leadership style and EP; to assess the relationship between transactional leadership style and EP in the FMCGs. Quantitative research survey design was adopted for the study; both primary and secondary sources of data were utilized during the investigation. The sample size of 233 was obtained from the estimated population using Rao soft online calculator at 5% error tolerance and 95% level of confidence. Data was collected via questionnaires and analyzed utilizing Simple Linear Regression (SLR) and Pearson product moment correlation (PPMC). It was discovered that there is a significant relationship between the various leadership styles and the performance of organisations. However, transactional leadership style was found to account for more influence on employee performance than other styles of leadership. Therefore, the study recommends the transactional style of leadership for managers of FMCGs in order to increase employee performance, ensure profitability and sustainability of the organisation.